Development of an Efficient Regeneration Protocol for Brassica carinata A. Braun through In vitro-derived Explants (Plant Tissue Culture and Biotechnology, 2025)
Brassica crops are globally recognized for their nutritional benefits and significant oil production, particularly in countries like Bangladesh. However, a significant challenge related to these crops is the elevated erucic acid content and increased glucosinolate levels, which limit their suitability for human consumption. Advanced technologies like genome editing and genetic transformation hold considerable promise for addressing these challenges; however, the establishment of effective regeneration systems is a crucial prerequisite for the successful application of these technologies. An effective and reproducible in vitro regeneration protocol for Brassica carinata A. Br. was developed using MS media supplemented with various concentrations and combinations of BAP, NAA and Kn. The MS medium supplemented with 3.0 mg/l BAP and 0.2 mg/l NAA produced the highest frequency of multiple shoot regeneration from both cotyledonary leaf with petiole and hypocotyl explants. The elongation of the shoot was concurrently optimized in the same media mix. Half-strength MS media supplemented with 0.3 mg/l IBA demonstrated greater efficacy in inducing root formation from excised in vitroderived shoots compared to other hormone supplements. After the successful establishment of well-developed root system, in vitro-regenerated plantlets were transferred to soil, resulting in the production of flowers and seeds. The R1 generation of plants was successfully established in field condition. The in vitro regeneration protocol for B. carinata developed in this study may serve as a foundation for future plant genetic transformation experiments.Plant Tissue Cult. & Biotech. 35(1): 155-162, 2025 (June)